Pengalaman Auditor dan Kepuasan Kerja Sebagai Pemoderasi Pengaruh TBP dan Profesionalisme Pada Kualitas Audit - Prabawati Suteja, I Gusti Diah Agung; Widhiyani, Ni Luh Sari (E-Jurnal Akuntansi; Vol 26 No 1 (2019), 2019)
This study aims to determine the effect of time budget pressure (TBP) and professionalism on audit quality with auditor experience and job satisfaction as moderating in KAP in Bali. The population in this study were all auditors who worked in KAP in Bali, amounting to 77 auditors. Determination of samples in this study using non probability sampling method with purposive sampling technique. The sample amounted to 42 auditors. The results of this research questionnaire were measured using a Likert scale. The data analysis technique used is Moderated Regression Analysis. The results of this study indicate that time budget pressure has a negative and significant effect on audit quality; professionalism has a positive and significant effect on audit quality; auditor experience weakens the effect of time budget pressure on audit quality, and strengthens the influence of professionalism on audit quality; and job satisfaction weakens the effect of time budget pressure on audit quality, and strengthens the influence of professionalism on audit quality. Keywords: time budget pressure, professionalism, auditor experience, job satisfaction, audit quality